Behaviour of coliform group in oxidation ponds - Shin, Hyun Kook; Omura, Tatsuo; Chongrak Polprasert; Vigneswaran, S.; CDG, Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1983)
Three different types of coliform bacteria, E. coli., C. freundii and Kebsiella sp. were the major coliform group found in ArT oxidation ponds. These coliform bacteria were isolated from a sewage sample of the oxidation ponds, and the behaviour of each coliform bacteria was investigated. E. coli was the major coliform group in the influent of the oxidation ponds, while Klebsiella sp. was the most abundant group in the effluent of the oxidation ponds. More than 99.9% of C. freundii and about 99.9% of E. coli were removed, but 99.7% of Klebsiella sp.was eliminated in the oxi- dation ponds. And also, most of the coliform bacteria were eliminated in facultative pond, around 99.5% of total coliform bacteria. Based on the results of laboratory test, pH, temperature, light inten- sity and coliphage were the major factors affecting.the die-off process of coliform bacteria. Among species, Klebsiella sp. was the most resistant bacteria to the several environmental conditions. E. coli and C. freundii were more susceptible. Coliphage was also a significant parameter affecting the die-off process of coliform bacteria. An increased destruction of coliform bacteria was obtained especially in such conditions as high temperature, a little acidic pH range and high dosage of coliphage.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1983
Keywords: Water quality management -- Nepal -- Phewa Lake